An Analysis of X-Band Calibrated Sea Clutter and Small Boat Reflectivity at Medium-to-Low Grazing Angles. (3rd November 2008) - Herselman, P. L.; Baker, C. J.; de Wind, H. J.
Abstract : The coherent temporal characteristics of medium-to-low grazing angle sea clutter and small boat reflectivity are considered for different radar waveforms under a range of environmental conditions and geometrical configurations. Accurate empirical modelling of sea clutter enables the inference of the local sea conditions from radar returns, pertinent for port safety and navigation. Understanding the dynamics and associated reflectivity of small boats, in addition to empirical sea clutter models, allows the development of advanced detection and tracking algorithms, which will improve the performance of surveillance and marine navigation radar against small boats. Work presented is based on the empirical analysis of data recorded with two calibrated, coherent, pulsed radar systems at X-band frequencies. Specifically, target echoes from small boats are included in the datasets and subsequent analysis.